Pengembangan Alat Peraga Mathdoku 5x5 untuk Meningkatkan Kemampuan Logika Siswa - Hriadi, Akbar; Wartini, Bella Septia; Sari, Dela Puspita; Firdaus, Raisya Adisty; Prassetya, Refki Meidi; Susanti, Elsa; Meryansumayeka, Meryansumayeka; Zulkardi, Zulkardi (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2024)
The aim of this research is to develop practical, valid and effective teaching aid to improve mathematical logic skills. The teaching aid developed is Mathdoku 5x5, which is a number puzzle game that is similar to Sudoku but also provides additional challenges so that players must use their counting skills. This research adopts the ADDIE development model which includes analysis, design, development, implementation and evaluation. Testing the validity of the teaching aids was carried out by involving experts at each stage of ADDIE, while testing the practicality and effectiveness of the teaching aids was carried out through trials on undergraduate to doctoral students and students. Data was collected through observation and interviews and analyzed descriptively. The research results show that Mathdoku 5x5 was successfully developed from the analysis to evaluation stages. The trial results showed that the test subjects could easily use this learning tool. These results show that this teaching aid is a practical tool. Furthermore, the use of Mathdoku 5x5 teaching aids has been proven to increase interest and ability in mathematical logic. This confirms that Mathdoku 5x5 can be classified as an effective teaching aid. Thus, it is concluded that Mathdoku 5x5 is a valid, practical, and effective teaching aid.